SUN-278 Neonatal Diabetes in an Infant with Heterozygous Mutation in KCNJ11 Gene - Kota, Archana (J Endocr Soc, 2019)
Background: Neonatal Diabetes is a rare form of monogenic diabetes that usually presents with hyperglycemia within the first 6 months of life. These infants usually are small for gestational age at birth. Unlike autoimmune diabetes, development of diabetic ketoacidosis (DKA) is extremely rare in this age group. We present a case of neonatal diabetes in a 3 month old, who presented in DKA. Genetic testing confirmed Kir6.2 subunit mutation. Clinical Case: A 3 month old African American male born to non-consanguineous parents presented with respiratory distress and poor weight gain. Initial blood testing showed serum glucose of 810 mg/dl and pH of 6.9 on an arterial blood gas analysis. Septic workup excluded infectious etiology. Antenatal history was significant for oligohydramnios. Birth history was unremarkable. He was born full term with birth weight of 2,579 grams. Physical examination was normal except for signs of severe dehydration. Both height and weight were below the 3(rd) percentile. Patient was started on DKA protocol. At the time of discharge, good glycemic control was obtained with a combination of short acting and long acting insulin. Genetic testing on our patient showed missense mutation c.601C>T on KCNJ11 gene on the Kir6.2 subunit encoding for beta cell ATP-sensitive potassium channel. Tight glycemic control was maintained with Lantus and Humalog for few months. He was then transitioned to oral Glyburide (0.2 mg/kg/day). He maintained good glycemic control and continued to develop age appropriate milestones. Conclusion: Neonatal diabetes is rare condition that usually presents with poor weight gain with in first few months of life. If remain undetected, these babies can present with DKA. Autoimmune markers are negative and genetic testing can help differentiate between temporary and permanent types. This particular mutation in our patient usually causes permanent diabetes and has a higher incidence of DEND (Developmental Delay, Epilepsy, and neonatal Diabetes). Unlike Type 1 DM, patients with KCNJ11 mutation are responsive to sulphonylureas and can be weaned off insulin. These infants need close neurological monitoring as well.